Lycorine inhibits MDA-MB-231 breast cancer cell proliferation, migration and invasion that are associated with Wnt/β-catenin signaling - Chen, Xia-Liang (Bangladesh Journal of Pharmacology, 2018)
This study was aimed to determine the effects of lycorine, a toxic crystalline alkaloid, on MDA-MB-231 breast cancer cells proliferation, migration and invasion, and to investigate the mechanism involved. The cells were cultured with different concentrations of lycorine in vitro. MTT assays were performed to determine the proliferation of cells. Transwell assays were performed to measure the migration and invasion of cells. The activation of Wnt/β-catenin signaling pathway and expression were assayed by Western blot. This study showed that proliferation, migration and invasion of MDA-MB-231 breast cancer cells could be inhibited by lycorine. Furthermore, we found that Wnt/β-catenin signaling was markedly blocked in MDA-MB-321 cells treated with lycorine. In conclusion, lycorine inhibits the proliferation, migration and invasion of MDA-MB-231 breast cancer cells that is associated with the suppression of Wnt/β-catenin signaling. Video Clip of Methodology: 5 min 39 sec: Click to watch